Ecuador in the face of gender violence: A study on the challenges and advances in the protection of human rights - Tapia Velez, Angel Enrique; Santistevan Chávez, Wanda del Consuelo; Montaño Ortiz, Jenniffer Angélica (Revista Universidad de Guayaquil, 2025)
The purpose of this study is to analize the impact of gender violence in Ecuador, identifying the main obstacles and advances in the protection and guarantee of fundamental rights. The methodology adopted a qualitative approach, through descriptive and analytical research. The hermeneutic method was used to interpret relevant legal texts and regulations, as well as the analytical-synthetic method to decompose and analyze current regulations and judicial practices. The data collection technique consisted of a documentary analysis of regulations, international treaties and reports from national and international organizations. The results revealed that gender violence in Ecuador seriously affects the human rights of the victims, manifesting itself in physical, psychological, sexual, economic and symbolic forms. Certainly, regulatory efforts have been made and the implementation of policies to control and prevent this type of violence has been promoted, however, the lack of knowledge about protection mechanisms increases the vulnerability and inequality of these women. Furthermore, many abandon their complaints due to fear, economic dependence and social pressure, which perpetuates their situation. In conclusion, the research revealed that, despite efforts to improve care for victims and the creation of legal channels for their protection, significant barriers persist such as cultural resistance and lack of awareness about gender equality, which makes it difficult to transform acts of violence.
Keywords: Gender violence; human rights; protection of victims; prevention of violence